New insights into the pathophysiology of dyslipidemia in type 2 diabetes. Issue 2 (April 2015) - Taskinen, Marja-Riitta; Borén, Jan
Abstract: Cardiovascular disease (CVD) remains the leading cause of morbidity and mortality for patients with type 2 diabetes, despite recent significant advances in management strategies to lessen CVD risk factors. A major cause is the atherogenic dyslipidemia, which consists of elevated plasma concentrations of both fasting and postprandial triglyceride-rich lipoproteins (TRLs), small dense low-density lipoprotein (LDL) and low high-density lipoprotein (HDL) cholesterol. The different components of diabetic dyslipidemia are not isolated abnormalities but closely linked to each other metabolically. The underlying disturbances are hepatic overproduction and delayed clearance of TRLs. Recent results have unequivocally shown that triglyceride-rich lipoproteins and their remnants are atherogenic. To develop novel strategies for the prevention and treatment of dyslipidaemia, it is essential to understand the pathophysiology of dyslipoproteinaemia in humans. Here, we review recent advances in our understanding of the pathophysiology of diabetic dyslipidemia. Highlights: The different components of diabetic dyslipidemia are not isolated abnormalities but closely linked metabolically to each other. The underlying disturbances are hepatic overproduction and delayed clearance of TRLs. Recent results show unequivocally that triglyceride-rich lipoproteins and their remnants are atherogenic.